Using Efficient Planning for Achieving Course Learning Outcomes in EFL Classes at Taif University - Awwad Othman Abdelaziz Ahmed (European Scientific Journal, ESJ, 2023)
This study investigates the efficiency and effectiveness of English as a Foreign Language (EFL) teachers in planning their lectures. The primary objective is to determine the extent to which teachers at the English Language Center (ELC) at Taif University, Kingdom of Saudi Arabia, successfully plan their lessons. A questionnaire was administered to a sample of 26 teaching staff, consisting of 13 males and 13 females. The results of a t-test conducted at a significance level of 0.05 reveal that class or lesson planning plays a crucial role in facilitating effective language teaching and learning. Adequate planning enables teachers to make informed decisions about lesson principles and helps in achieving desired learning outcomes. In order to make informed decisions on the selection of topics, scenarios, methods, techniques, and procedures for their courses, educators are required to adopt a systematic approach. Educators have the potential to enhance the quality of their instructional sessions and optimize educational achievements among learners through the conscientious observance of these facets of lesson preparation. This study contributes to the existing literature on EFL teaching practices by providing insights for educators to improve their instructional planning strategies.Overall, the findings emphasize the significance of thorough planning in EFL instruction and highlight its impact on successful teaching and learning experiences.